BENTUK INTERAKSI PADA PEDAGANG KAKI LIMA DI PASAR TONDANO KELURAHAN WAWALINTOUAN KECAMATAN TONDANO BARAT - Eleni Gea; zoni hengki singal; Abdul Rasyid umaternate (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2022)
The purpose of this study was to describe the form of social interaction among street vendors in the Tondano market, Minahasa district. The method used in this study is a qualitative method, using a descriptive approach that aims to describe and accurately describe the systematic and actual forms of social interaction at street vendors in the Tondano market using observation, documentation, and interviews as data collection techniques. The results show that the form of interaction between street vendors in the Tondano market is very close, it can be seen how they work together, care for each other between fellow street vendors and also feel what is felt by fellow street vendors in the Tondano market. Competition that occurs between street vendors is a competition that takes place in a healthy manner by not dropping the merchandise of other street vendors and if there is a problem, whether there is a difference of opinion between street vendors, they choose to first solve the problem amicably or discuss it well. and do not exaggerate the problem because they realize that they are the same trader and they also realize that they need each other. From the results of the research that has been stated, it is hoped that it can be useful for lecturers, students, and prospective students, in order to develop education, especially at Manado State University